تأثير درجة التوافق النفسي الاجتماعي في تحسين مستوى الأداءالمهاري في كرة القدم دراسة لصنف أشبالدراسة ببعض الأندية الرياضية لولاية البويرة-المدية - محمد, مهدي (دفـاتر المـــــــــــخبـر; No 14 (2015): مجلة دفاتر, 2018)
الملخص: يرتبط مستوى ونوعية الأداء المهاري بالحالة النفسية والاجتماعية للفرد والفريق، وهذا ما يعبر عنه بالتوافق النفسي والاجتماعي الذي يعتبر بأبعاده من العمليات الهامة في حياة الإنسان. وبما أن اللاعب عنصر أساسي في هذه الدراسة فقد قمنا بدراسة  خاصة للمدربين  واللاعبين لمعرفة المميزات النفسية والاجتماعية التي قد تسهم في تحسين مستوى الأداء المهاري أثناء المنافسة. تهدف الدراسة إلى معرفة مدى تأثير درجة التوافق النفسي الاجتماعي على مستوى الأداء المهاري أثناء منافسة كرة القدم فئة أشبال. ويمكن القول بأنه تم التأكد من الفرضية العامة للدراسة، وتبين لنا مدى أهمية التوافق النفسي والاجتماعي بالنسبة للنشاط الرياضي بصفة عامة ورياضة كرة القدم بصفة خاصة،حيث تساعد على اللاعب على فهم المهارات النفسية الاجتماعية التي تمكنه من بناء علاقات اجتماعية داخل وخارج الفريق، وتعمل على تحقيق العلاقات الاجتماعية السوية بين أفراد الفريق الواحد لغرض روح التعاون وروح الجماعة، فضلا عن توفير جو اجتماعي داخل الحصص الرياضية. Summary: The level and quality of skillful performance is related to the psychological and social state of the individual and the team, which is expressed by the psychological and social compatibility which is considered to be one of the most important processes in human life. Since the player is a key element in this study, we have conducted a special study for trainers and players to know the psychosocial features that may contribute to improving skill performance during competition. The aim of the study is to determine the extent to which the degree of psycho-social compatibility affects the level of skill performance during football competition. It can be said that the general hypothesis of the study was confirmed, and showed us the importance of psychological and social compatibility for sports activity in general and football in particular, which helps the player to understand the psychosocial skills that enable him to build social relations within and outside the team, To achieve the proper social relations between the members of one team for the purpose of the spirit of cooperation and spirit of the community, as well as to provide a social atmosphere within the sports quotas